An appraisal on synthetic and pharmaceutical perspectives of pyrazolo[4, 3-d]pyrimidine scaffold. Issue 2 (15th January 2018) - Cherukupalli, Srinivasulu; Hampannavar, Girish A.; Chinnam, Sampath; Chandrasekaran, Balakumar; Sayyad, Nisar; Kayamba, Francis; Reddy Aleti, Rajeshwar; Karpoormath, Rajshekhar
Graphical abstract: Highlights: Pyrazolo[4, 3- d ]pyrimidine: Nitrogen containing bicyclic heterocyclic ring with diverse biological activities. Synthetic strategies for variously substituted pyrazolo[4, 3- d ]pyrimidine. The numerous pharmacological activities of pyrazolo[4, 3- d ]pyrimidine has been discussed. SAR of pyrazolo[4, 3- d ]pyrimidine scaffold for miscellaneous activities has been explained. This review will be helpful for medicinal chemists in designing future drugs. Abstract: Pyrazolo[4, 3- d ]pyrimidine, a fused heterocycle bearing pyrazole and pyrimidine portions has gained a significant attention in the field of bioorganic and medicinal chemistry. Pyrazolo[4, 3- d ]pyrimidine derivatives have demonstrated numerous pharmacological activities particularly, anti-cancer, anti-infectious, phosphodiesterase inhibitors, adenosine antagonists and cytokinin antagonists etc. This review extensively unveils the synthetic and pharmacological diversity with special emphasis on structural variations around pyrazolo[4, 3- d ]pyrimidine scaffold. This endeavour has thus uncovered the medicinal worthiness of pyrazolo[4, 3- d ]pyrimidine framework. To the best of our knowledge this review is the first compilation on synthetic, medicinal and structure activity relationship (SAR) aspects of pyrazolo[4, 3- d ]pyrimidines since 1956.